Developmental allometry and paediatric malaria - Billig Erica MW; O'Meara Wendy P; Riley Eleanor M; McKenzie F Ellis (Malaria Journal, 2012)
Abstract WHO estimates that 80% of mortality due to malaria occurs among infants and young children. Though it has long been established that malaria disproportionately affects children under age five, our understanding of the underlying biological mechanisms for this distribution remains incomplete. Many studies use age as an indicator of exposure, but age may affect malaria burden independently of previous exposure. Not only does the severity of malaria infection change with age, but the clinical manifestation of disease does as well: younger children are more likely to suffer severe anaemia, while older children are more likely to develop cerebral malaria. Intensity of transmission and acquired immunity are important determinants of this age variation, but age differences remain consistent over varying transmission levels. Thus, age differences in clinical presentation may involve inherent age-related factors as well as still-undiscovered facets of acquired immunity, perhaps including the rates at which relevant aspects of immunity are acquired. The concept of "allometry" - the relative growth of a part in relation to that of an entire organism or to a standard - has not previously been applied in the context of malaria infection. However, because malaria affects a number of organs and cells, including the liver, red blood cells, white blood cells, and spleen, which may intrinsically develop at rates partly independent of each other and of a child's overall size, developmental allometry may influence the course and consequences of malaria infection. Here, scattered items of evidence have been collected from a variety of disciplines, aiming to suggest possible research paths for investigating exposure-independent age differences affecting clinical outcomes of malaria infection.